Tetrabenzononacene: "Butterfly Wings" Stabilize the Core. Issue 5 (17th December 2019) - Müller, Matthias; Maier, Steffen; Tverskoy, Olena; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: In combination with bulky substituents at the core, fourfold benzannulation at the cata ‐positions stabilizes a nonacene sufficiently to allow its isolation and characterization by 1 H NMR and X‐ray analysis. The four benzo units blueshift the absorption spectrum in comparison to a solely linear nonacene, but significantly increase the stability in the solid state. Abstract : Attachment of four benzo units electronically stabilizes a nonacene core without heteroatom substitution at/on the aromatic backbone. The four benzo units blueshift the absorption spectrum in comparison to a linear nonacene and significantly increase the stability in the solid state.